SAT0212 Sustained Response to Mavrilimumab in Rheumatoid Arthritis Patients VIA Suppression of Macrophage and T Cells. (9th June 2015) - Guo, X.; Sinibaldi, D.; Kuziora, M.; Brohawn, P.; Ryan, P.C.; Bay-Jensen, A.C.; Karsdal, M.A.; Roskos, L.K.; White, W.I.
Abstract : Background: Mavrilimumab is a fully human monoclonal antibody targeting granulocyte-macrophage colony-stimulating factor receptor α (GM–CSFR-α). It is the first therapeutic to target this pathway in the treatment of rheumatoid arthritis (RA). A Phase IIb clinical trial (EARTH EXPLORER 1; NCT01706926 ) 1 of patients with moderate to severe RA has demonstrated mavrilimumab to be an efficacious and well-tolerated treatment option for RA. Objectives: We assessed peripheral biomarkers and pathophysiologic pathways modulated by mavrilimumab in association with clinical response through GM–CSFR-α blockade in RA patients. Methods: In a 24-week, randomized controlled study, RA patients received subcutaneous mavrilimumab (30, 100, or 150 mg every other week [eow]) or placebo, both in combination with methotrexate. Serum concentrations of 19 RA-associated proteins, as well as 6 protease-derived protein fragments, from 326 RA patients were measured at baseline and at 5 time points post-administration. Affymetrix HGU133Plus2 arrays were used to measure gene expression changes in whole blood of RA patients receiving mavrilimumab 100 or 150 mg eow, or placebo. Results: Several proteins demonstrated significant down-regulation at Days 8, 15, 29, 85, and 169 after mavrilimumab 100 mg and/or 150 mg eow treatment, compared with placebo, including CRP, SAA, IL-6, macrophage-derived chemokine (CCL22), IL-2RA, MMP3, and VEGF (Mann-Whitney U test, p <0.05). Spearman's correlation analysis indicated significant associations between the suppression of 7 proteins and clinical response (DAS28–CRP reduction) at Day 169 following mavrilimumab administration (p <0.05). While the suppression of CCL22, MMP3, and IL-6 may reflect a direct effect of GM–CSFR blockade on the production of pro-inflammatory mediators by myeloid cells, IL-2RA down-regulation suggests an indirect suppressive effect of mavrilimumab on T-cell activation. Furthermore, mavrilimumab induced significant suppression of MMP-degraded type I collagen (C1M) and citrullinated vimentin (VICM), suggesting a beneficial effect of mavrilimumab on soft tissue damage and auto-antigen formation in RA. Both C1M and VICM down-regulation were more pronounced in ACR20 responders than non-responders at Day 169 ( p <0.05). Consistent with serum proteomics results, whole blood gene expression analyses demonstrated suppression of 382 transcripts at Day 196 after mavrilimumab administration (FDR<0.05), which were enriched for macrophage activity in RA and IL-17/IL-22 signaling pathways based on Ingenuity Pathway Analysis. Transcript concentrations of 2 protein citrullination enzymes, MMP9 and MMP25, were down-regulated by mavrilimumab in ACR20 responders, which may be related to suppression of VICM after GM–CSFR blockade. Conclusions: Our analyses indicate that the sustained efficacy of mavrilimumab in RA may result from both direct effects on macrophages and indirect effects on T-cell activation after GM–CSFR blockade. Further, protein citrullination and extracellular matrix degradation were suppressed by mavrilimumab, suggesting tissue damage in RA may be alleviated by mavrilimumab therapy. References: Burmester GR, et al. Arthritis Rheum 2014;22(11 Suppl):S1231–S1232. Disclosure of Interest: X. Guo Shareholder of: AstraZeneca, Employee of: MedImmune, D. Sinibaldi Shareholder of: AstraZeneca, Employee of: MedImmune, M. Kuziora Shareholder of: AstraZeneca, Employee of: MedImmune, P. Brohawn Shareholder of: AstraZeneca, Employee of: MedImmune, P. Ryan Shareholder of: AstraZeneca, Employee of: MedImmune, A. Bay-Jensen Grant/research support from: MedImmune, M. Karsdal Grant/research support from: MedImmune, L. Roskos Shareholder of: AstraZeneca, Employee of: MedImmune, W. White Shareholder of: AstraZeneca, Employee of: MedImmune